Radiation-Hydrodynamic Simulations of Core-collapse Supernovae with 6 Dimensional Boltzmann Neutrino Transport. (May 2019) - Nagakura, Hiroki; Furusawa, Shun; Togashi, Hajime; Sumiyoshi, Kohsuke; Yamada, Shoichi
Abstract: Core-collapse supernovae (CCSNe) are intrinsically multi-scale, multi-physics and multi-dimensional phenomena. Because of the enormous complexity, the first-principles numerical simulations under realistic input physics are strongly required to uncover the explosion mechanism, predict observational signals (neutrinos, gravitational waves and electromagnetic waves) and prove physical state in extremely hot and dense matter of supernova core. We have tackled the development of multi-dimensional radiation-hydrodynamic code with full Boltzmann neutrino transport and performed several scientific CCSNe simulations in the last few years. In this article, we report the recent progress of our CCSNe numerical simulations with the most up-to-date equation-of-state (EOS) and nuclear weak interactions. We also present preliminary results of non-rotating CCSNe simulations in spatial axisymmetry.